Al DS - Precautions for Ophthalmic Practice - Levy, B (Canadian Journal of Optometry, 2021)
Since 1981 a new and much publicized infection (AIDS) has come to the attention of the health care community and the public. The reason for the tremendous publicity generated by the disease is the devastating outcome once diagnosis has been made, and the rapid rate at which it appears to be spreading.